Factors Affecting Seroconversion Rates in Cattle Vaccinated with Two Commercial Inactivated BTV‐8 Vaccines Under Field Conditions. Issue 2 (6th June 2014) - Vitale, N.; Radaelli, M. C.; Chiavacci, L.; Paoletti, M.; Teodori, L.; Savini, G.
Summary: The immunogenicity of two inactivated bluetongue virus serotype 8 (BTV‐8) vaccines was evaluated in 880 cattle under field conditions. The effect of selected factors on vaccine performance was also analysed at the herd and animal levels (vaccine, herd size and production, age, sex, time interval between vaccination and blood sampling and veterinary training). The immunogenicity elicited by vaccination with the two vaccines was monitored with the aid of a competitive enzyme‐linked immunosorbent assay (c‐ELISA) and serum neutralization test (SNT). To investigate whether the selected factors influenced seroconversion at the herd and animal levels, a multilevel logistic regression model developed in a mixed model was applied. Of the 880 cattle vaccinated, 76.0% yielded BTV c‐ELISA antibodies, whereas only 25.0% seroconverted based on SNT. Type of vaccine (odds ratio [OR] 4.5; 95% confidence interval [CI], 2.2–9.0 for SNT and OR 3.5; 95% CI, 2.1–5.9 for c‐ELISA), veterinary training in vaccine administration (OR 8.1; 95% CI, 4.7–14.1 for SNT and OR 2.4; 95% CI, 1.3–4.2 for c‐ELISA), animal age (OR 1.4; 95% CI, 1.1–1.8 for SNT and OR 1.7; 95% CI, 1.4–2.1 for c‐ELISA) and days between first vaccine administration and blood collection (OR 1.9; 95% CI, 1.1–3.1 for SNT and OR 2.6; 95% CI, 1.7–3.8 for c‐ELISA) were the major factors affecting vaccine performance under field conditions. This is the first study to use multilevel logistic regression in the evaluation of selected risk factors affecting BTV‐8 vaccine performance in cattle.